2008
DOI: 10.1051/apido:2008037
|View full text |Cite
|
Sign up to set email alerts
|

Using geometric morphometrics and standard morphometry to discriminate three honeybee subspecies

Abstract: -Honeybee (Apis mellifera) subspecies usually are distinguished by standard morphometry methods, based mainly on multivariate analysis of distances and angles. Recently another method of statistical analysis of shape, geometric morphometrics, has been developed. The new method is based on characteristic points described by Cartesian coordinates. The two methods were used here to discriminate three honeybee subspecies (A. m. mellifera, A. m. carnica and A. m. caucasica) according to forewing venation. Forewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
136
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 17 publications
4
136
0
12
Order By: Relevance
“…The species status of kawaii is further confounded by molecular evidence for its hybridisation with haughtoni, with which it occurs sympatrically in the Hex River Mountains (Switala 2013;Switala et al 2014). Geometric morphometrics have been successfully used to distinguish honeybee subspecies (Apis mellifera Linnaeus, 1761; Hymenoptera: Apidae) (Tofilski 2008) and to identify cryptic Nebriola ground beetle species (Coleoptera: Carabidae) (Roggero et al 2013), and similar methods could shed light on Colophon systematics.…”
Section: Colophon Morpho-taxonomymentioning
confidence: 99%
“…The species status of kawaii is further confounded by molecular evidence for its hybridisation with haughtoni, with which it occurs sympatrically in the Hex River Mountains (Switala 2013;Switala et al 2014). Geometric morphometrics have been successfully used to distinguish honeybee subspecies (Apis mellifera Linnaeus, 1761; Hymenoptera: Apidae) (Tofilski 2008) and to identify cryptic Nebriola ground beetle species (Coleoptera: Carabidae) (Roggero et al 2013), and similar methods could shed light on Colophon systematics.…”
Section: Colophon Morpho-taxonomymentioning
confidence: 99%
“…In Apis mellifera, specimens have been accurately assigned to the subspecies level Tofilsky 2008;Francoy et al 2009b), workers and males were correctly identified in stingless bees (Francoy et al 2009a), cryptic species were detected in Plebeia remota (Francisco et al 2008), and genetic variability among populations was also evaluated using this type of analysis (Mendes et al 2007;Kandemir et al 2009). Even though it is a simple technique for which only a stereomicroscope, a digital camera and a computer are needed, geometric morphometrics gives clear results that can be helpful as a first step towards answering questions that are normally resolved using molecular methods, which are much more expensive, require specialized personal and well-equipped laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out on Apis mellifera to differentiate subspecies regarding geometric morphometrical features, using programs of automatic identification (francoy et al, 2006, 2008Tofilski, 2008). This species is described as an example of a bee species endowed with important features, such as fast development and adaptation, rusticity, high capacity for honey and propolis production, better capacity for food source identification, efficient pollinating features and disease resistance (Gonçalves, 2006).…”
mentioning
confidence: 99%
“…Morphometrics involves a group of techniques that allow to deduct evolutionary processes from spatial standards and to test these theories to explain the "Africanization" of Apis mellifera populations in the Neotropical region (Diniz-filho & Malaspina, 1995), Variation morphogeometrics of Africanized honey bees... particularly, the geometric morphometrics that analyzes the wing morphometry to provide information for the identification of honeybee populations (Tofilsky, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation